Globalization and the politics of development in the Middle East - Henry, Clement M. (Cambridge University Press, 2001)
At the beginning of the twenty-first century countries in the Middle East and North Africa are contending with the challenges of economic globalization. In a straightforward and, at times, irreverent analysis of the regions' response to these challenges, the authors demonstrate that there is a direct correlation between economic performance and democratization: the more liberal the polity, the more effective its economy in responding to globalization. This is an original and incisive approach to the political economy of the Middle East that will be an essential purchase for students and policy-makers.